LIFE, SCIENTIFIC AND PEDAGOGICAL ACTIVITY OF ACADEMICIAN D.K. ZABOLOTNY IN ODESA (28.12.1866-15.12.1929) - В. О. Кузнецов; Н. В. Кузнецова (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2007)
On the basis of studying the archives materials of Institute of Archivestudying NLU named after V.I. Vernadskiy AN Ukraine, National Archive Odesa region, private archives of Odessa University teachers and literature sources the main events of the scientific and pedagogical (activity) of D.K. Zabolotny, connected with the years, spent in Odesa in different time have beene investigated.